EFFECTIVENESS OF DIGITAL EDUCATION AND TRAINING FOR TEACHERS AT STATE TSANAWIYAH MADRASAH 3, PEKANBARU CITY - Nurus Sakinah; Simson Ginting; Janry Simanungkalit (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
The transformation of education in the era of the Industrial Revolution 4.0 demands that madrasa teachers possess digital competencies that can adapt to technological advancements. However, the implementation of digital-based training in public madrasas still faces several challenges, such as limited infrastructure, varying levels of human resource readiness, and issues regarding program effectiveness. This study aims to analyze and interpret This study aims to analyze and interpret the effectiveness of digital education and training (diklat) for teachers at MTsN 3 Pekanbaru City, focusing on program implementation success, goal achievement, participant satisfaction, input-output comparison, and overall goal attainment. The research employs a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis of the digital training programs conducted at the madrasa. The findings reveal that digital training has improved teachers’ digital literacy and motivation, particularly among younger educators. Nevertheless, its overall effectiveness remains constrained by inadequate institutional support, generational skill gaps, and limited technological facilities. This research contributes to the literature on digital training effectiveness in Islamic schools and provides recommendations for developing more contextual, adaptive, and sustainable training models.